Bedside Ultrasound of the Neck Confirms Endotracheal Tube Position in Emergency Intubations - Hoffmann, B.; Gullett, J. P.; Hill, H. F.; Fuller, D.; Westergaard, M. C.; Hosek, W. T.; Smith, J. A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: In controlled environments such as the operating room, bedside ultrasound (BUS) of the neck has shown high accuracy for distinguishing endotracheal (ETI) from esophageal intubations. We sought to determine the accuracy of BUS for endotracheal tube (ETT) position in the emergency department (ED) setting.Materials and Methods: We assessed the utility of BUS in a single-center observational study in an ED setting. BUS was performed either simultaneously with ED intubation (S/ED), within < 3 minutes of ED intubation (A/ED), or in < 3 minutes of patient’s ED arrival after pre-hospital intubation (A/EMS). Trained ED providers performed BUS; intubators were blinded to ultrasound findings. We used Cormack and Lehane categories (CL) to classify intubation attempts as “easy” (CL-I/II), “moderate” (CL-III) and “difficult” (CL-IV). Additional data included the diagnostic accuracy of the sonographer and intubator compared to the clinical outcome, anatomy identified by sonography and time to diagnosis.Results: During a 10-month period, 89 subjects with 115 intubation attempts were included in the study, and 86 patients/101 attempts with complete data were used in the study (63-easy, 19-moderate, 19-difficult). The sonographers achieved 100 % accuracy with respect to determining the correct ETT position utilizing an anterior neck approach, while the intubators’ accuracy in assessing correct tube location was 97 % compared to the clinical outcome. A blinded review of sonography findings confirmed all BUS anatomical findings. A sonographically empty esophagus was 100 % specific for endotracheal intubation, and a “double trachea sign” was 100 % sensitive and 91 % specific for esophageal intubation. The sonographic time to diagnosis was significantly faster than the intubator time to diagnosis (“easy” p < 0.001; n = 47; “moderate” p = 0.001; n = 15; “difficult” p < 0.001; n = 19); Wilcoxon test; A/EMS cases excluded).Conclusion: In this emergency setting, ultrasound determined ETT locations rapidly with 100 % accuracy and independently of the CL-category.
Keywords: emergency ultrasound; esophageal intubation; ultrasound-guided procedures; larynx; throat